IMPROVING STUDENTS’ ENGLISH SPEAKING ABILITY THROGH THE FREE STORY METHOD WITH PICTURE CARD MEDIA - Fredy Yunanto (Universitas Pahlawan Tuanku Tambusai, 2022)
This study focuses on student problems related to limited ability to communicate in English in class VII-A Pamekasan Middle School. The Free Story method is used in this study, along with picture card media. This study used a classroom action research design which was carried out in two cycles. The results showed that in cycle I, 18 students (66.67%) had the same or higher speaking ability score than the KKM, while nine students (33.33%) had lower scores than the KKM. Because these results did not meet the success criteria, namely at least 85% of students had scores equal to or above the KKM, the research would continue in the next cycle by first revising some of the results. Keywords: Talking, free stories, picture cards.